Tinjauan Yuridis Terhadap Undang-Undang Perlindungan Satwadi Kota Surakarta(Studi Kasus di Pengadilan Negeri surakarta) - Kurniawati, Ismi; , Hartanto, S.H., M.Hum (2016)
To protect wildlife from extinction has been regulated in Law No. 5 of 1990 on Conservation of Natural Resources and Ecosystem, particularly clause 21 verse (1) and verse (2) as well as clause 33 verse (3), which carries a maximum imprisonment of 5 years and a fine of 100 million rupiah (clause 40 verse (2)). Law enforcement against the rules above there are various obstacles because the perpetrators officials and rich people, the lack of facilities and infrastructure owned by officers police forces, and the low participation of the public to report violations of the crime. Habitats and the extinction of some species of these animals during the many that have been damaged or accidentally damaged by various act of a group of people who are not responsible. The biggest threat to the preservation of these animals is the human activity, mainly the conversion of forest land for construction purposes such as agriculture, mining, settlement expansion, transmigration and other infrastructure development.